(untitled) - Kvesitadze, G. I (Berlin, 2006)
Includes bibliographical references and index
Keywords: Phytoremediation; Plants -- Metabolism; Metabolic detoxification; Cây trồng -- Sự trao đổi chất; Công nghệ kiểm soát ô nhiễm -- Phytoremediation; Thực vật cải tạo môi trường